Interaction of the modulated electron beam with plasma: kinetic effects - Anisimov, I.O.; Kiyanchuk, M.J.; Soroka, S.V.; Velykanets, D.M. (Вопросы атомной науки и техники, 2007)
Evolution of the velocity distribution functions of plasma and beam electrons during modulated electron beam propagation in homogeneous and inhomogeneous plasma was studied numerically. Velocity distribution function of plasma electrons at the late time moments strongly differs from initially Maxwellian one. In the regions of strong electric field plasma electrons’ bunches are formed. Comparison of distribution functions of beam electrons for modulated and non-modulated beams shows that deep initial modulation suppresses resonant instability development. In the inhomogeneous plasma acceleration of electrons in the plasma resonance point can be observed. Числовими методами досліджена еволюція функції розподілу електронів плазми та пучка за швидкостями при поширенні модульованого електронного пучка в однорідній і неоднорідній плазмі. Функція розподілу для електронів плазми в пізні моменти часу суттєво відрізняється від початкової максвеллівської. В областях сильного електричного поля утворюються згустки електронів плазми. Порівняння функцій розподілу електронів пучка для модульованих і немодульованих пучків показує, що глибока початкова модуляція придушує розвиток резонансної нестійкості. В неоднорідній плазмі може спостерігатися прискорення електронів у точці локального плазмового резонансу. Численно исследована эволюция функции распределения электронов плазмы и пучка по скоростям при распространении модулированного электронного пучка в однородной и неоднородной плазме. Функция распределения для электронов плазмы в поздние моменты времени существенно отличается от начальной максвелловской. В областях сильного электрического поля образуются сгустки электронов плазмы. Сравнение функций распределения электронов пучка для модулированных и немодулированных пучков показывает, что глубокая начальная модуляция подавляет развитие резонансной неустойчивости. В неоднородной плазме может наблюдаться ускорение электронов в точке локального плазменного резонанса.